Acculturation, ethnic identity, and psychological well-being of Albanian-American immigrants in the United States. Issue 4 (2nd October 2018) - Balidemaj, Albina; Small, Mark
ABSTRACT: This study examined the relationship between acculturation, ethnic identity, and psychological well-being of the Albanian-American immigrant community in United States. A total of 139 Albanian-American immigrants aged 21–35 years old participated in the study. In order to utilize the data, participants filled out four different surveys, including a demographic questionnaire, the Multigroup Ethnic Identity Measure (MEIM), the Vancouver Index of Acculturation (VIA), and Ryff's Psychological Well-Being scale. A correlational design relying on cross-sectional survey data and multiple regression analysis was used to study the correlations between acculturation, ethnic identity, and psychological well-being. The results showed that ethnic identity, acculturation, and psychological well-being were positively correlated to each other. In addition, the results showed that both ethnic identity and acculturation affected the psychological well-being of Albanian-American immigrants in the United States. This relationship was further moderated by gender and length of residency in the United States and mediated through graduate school education. The results of this study will help clinicians, social workers, and policy makers that work with immigrants to better understand the psychological consequences of immigration due to acculturation and ethnic identity factors.